Psychosocial factors and medication adherence among recipients of vascularized composite allografts - Sarah E Van Pilsum Rasmussen; Alexander Ferzola; Carisa M Cooney; Jaime T Shores; WP Andrew Lee; Emily Goldman; Christina L Kaufman; Gerald Brandacher; Dorry L Segev; Macey L Henderson (SAGE Open Medicine, 2020)
Objectives: Psychosocial factors are important predictors of medication adherence, and subsequently graft survival, in solid organ transplantation. Early experiences suggest this may also be the case in vascularized composite allotransplantation. Methods: Using validated tools, we surveyed upper extremity transplant recipients at two centers to assess depression (Patient Health Questionnaire-9), personality (Ten-Item Personality Inventory), anxiety (Generalized Anxiety Disorder 7-Item Scale), post-traumatic stress disorder (Primary Care Post-Traumatic Stress Disorder Screen for Diagnostic and Statistical Manual of Mental Disorders , 5th Edition), and social support (Multidimensional Scale of Perceived Social Support). Medication adherence among vascularized composite allotransplantation recipients at two centers was assessed by a member of the clinical research team using the recipients’ medical records. Results: Medication adherence was reported for 12 vascularized composite allotransplantation recipients, and 9 vascularized composite allotransplantation recipients completed psychosocial assessments. Most recipients were believed to be adherent to their immunosuppression, however, three recipients were believed to be non-adherent and a member of the clinical team had discussed non-adherence at least once with five recipients. Results from the psychosocial assessment (n = 9) indicated that eight participants had high levels of social support, and eight demonstrated high levels of conscientiousness which have been associated with better medication adherence in solid organ transplantation. However, three participants demonstrated mild anxiety, two demonstrated minimal symptoms of depression, and one demonstrated post-traumatic stress disorder which have been associated with worse medication adherence in solid organ transplantation. Conclusion: These findings lay the groundwork for future assessments of the role psychosocial factors play in facilitating medication adherence and broader transplant outcomes.